Study Of Effects Of Cervıcal Headgear On Cranıofacıal Structures In Treatment Of Dental And Skeletal Class I Anomalıes - Semra Şahin Özer; Jalan Devecioğlu Kama; Sedat Baran; Orhan Hamamcı (Galenos Yayinevi, 2001)
The aim of this study was to study the changes on craniofacial structures as a result of extraction of four first premolars and use of modified Edgewise technique and servical headgear in patients with dental and skeletal CI.I anomaly. Treatment group of the study is composed of 16 patients who have applied to the Department of Orthodontics; Faculty of Dentistry of Dicle University and control group is composed of 10 patients from the archive of the Department of Orthodontics, Faculty of Dentistry of Ankara University. Following measurement of 20 parameters on cephalometric films, the data has been compared with Student t test. The treatment has indicated statistically significant changes on SNA angle, anterior and posterior face heights and upper incisors and molar alveolar heights (p<0.01).